Прогностичка вредност нивоа сира Анг-5 и ШХЛП1 за ризик и прогнозу компликација код пацијената са акутним мозгањим инфарктом: Нивои серума Анг-5 и ШХЛП1 код АЦИ - Zhang, Qian; Zhang, Xuehan; Wang, Shuli; Xu, Wenqiong; Wu, Lirong (Journal of Medical Biochemistry, 2026)
Objective To investigate the levels of ‌Survival of Motor Neurons Homolog Protein 1‌ (SHLP1) and serum Angiopoietin 5 (‌Ang-5) in patients with acute cerebral infarction (ACI) who also have brain-heart syndrome (BHS). Methods The concurrent group consisted of 208 patients with BHS-complicated ACI who were hospitalized between January 2023 and June 2025, whereas the nonconcurrent group consisted of 220 patients with simple ACI who visited the hospital during the same time frame. The serum levels of SHLP1 and ‌Ang-5 in the patients were assessed using an enzyme-linked immunosorbent assay. Pearson correlation analysis was used to investigate the relationships between the serum levels of ‌Ang-5 and SHLP1 in patients with ACI complicated by BHS and the following indicators: left ventricular ejection fraction (LVEF), cardiac troponin I (cTnI), N-terminal pro-brain natriuretic peptide (NT-proBNP), creatine kinase isoenzyme (CK-MB), and others. The diagnostic value of serum ‌Ang-5 and SHLP1 for BHS in patients with acute coronary insufficiency was evaluated using receiver operating characteristic (ROC) curves. Results Serum SHLP1 level and LVEF were lower in the concurrent group than in the nonconcurrent group, although serum CK-MB, NT-proBNP, cTnI, and ‌Ang-5 levels were greater in the concurrent group. Statistically, the differences were substantial (P<0.05). The serum SHLP1 level of patients with ACI and BHS was found to be positively connected with LVEF (P<0.05) and negatively correlated with CK-MB, NT-proBNP, and cTnI levels, according to the Pearson correlation analysis. LVEF was adversely linked (P<0.05) with the serum ‌Ang-5 level, whereas CK-MB, NT-proBNP, and cTnI levels were positively correlated. ‌Ang-5, CK-MB, NT-proBNP, and cTnI were risk factors for BHS in ACI patients (P<0.05), whereas higher serum SHLP1 levels and higher LVEF were protective factors for BHS in ACI patients (P<0.05), according to the results of multivariate logistic regression analysis. Based on the results of the ROC curve analysis, the area under the curve (AUC) for the combined diagnosis of blood ‌Ang-5 and SHLP1 for ACI patients with BHS was 0.927, greater than the AUC for serum ‌Ang-5 and SHLP1 alone (Z = 3.340, P = 0.001; Z = 3.541, P < 0.001). Conclusion Patients with ACI complicated by BHS had low serum SHLP1 levels but high serum ‌Ang-5 levels. The diagnostic value for ACI complicated by BHS can be increased by the combined detection of these two signs.